2020
DOI: 10.1093/molbev/msaa196
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Higher-Order Epistasis in Drug Resistance

Abstract: We studied five chemically distinct but related 1,3,5-triazine antifolates with regard to their effects on growth of a set of mutants in dihydrofolate reductase (DHFR). The mutants comprise a combinatorially complete data set of all 16 possible combinations of 4 amino acid replacements associated with resistance to pyrimethamine in the malaria parasite Plasmodium falciparum. Pyrimethamine was a mainstay medication for malaria for many years, and it is still in use in intermittent treatment during pregnancy or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…For some studies, the mutations were accumulated through directed evolution or protein engineering of a novel function (phosphotriesterase, PTE; β-lactamase, OXA-48; nitroreductase, NfsA) 13,[22][23][24] . For the remaining studies, the positions were identified from naturally occurring evolutionary trajectories, either through a retrospectively identified path using ancestral sequence reconstruction (methyl-parathion hydrolase, MPH) 14,25 , the presence of clinically relevant mutations (dihydrofolate reductase, DHFR and β-lactamase, TEM-1) 11,[26][27][28] , or in the case of alkaline phosphatase (AP), by using previously characterised active site residue mutations 29 . The final dataset consisted of 56 unique mutations, of which 54 are located within the protein open reading frame, and two are located in a promoter region (in DHFR and TEM-1) 11,23 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For some studies, the mutations were accumulated through directed evolution or protein engineering of a novel function (phosphotriesterase, PTE; β-lactamase, OXA-48; nitroreductase, NfsA) 13,[22][23][24] . For the remaining studies, the positions were identified from naturally occurring evolutionary trajectories, either through a retrospectively identified path using ancestral sequence reconstruction (methyl-parathion hydrolase, MPH) 14,25 , the presence of clinically relevant mutations (dihydrofolate reductase, DHFR and β-lactamase, TEM-1) 11,[26][27][28] , or in the case of alkaline phosphatase (AP), by using previously characterised active site residue mutations 29 . The final dataset consisted of 56 unique mutations, of which 54 are located within the protein open reading frame, and two are located in a promoter region (in DHFR and TEM-1) 11,23 .…”
Section: Resultsmentioning
confidence: 99%
“…28 explored 15 inhibitors for the same set of four mutations c Two separate mutational trajectories for the same protein and substrate d Ref. 26 explored four mutations using five different substrates; ref. 27 explored both kcat/KM and KI for two mutational trajectories e Ref.…”
Section: Resultsmentioning
confidence: 99%
“…2013, 2018; Lozovsky et al. 2020). “Order” corresponds to the number of actors involved in an interaction.…”
Section: Methodsmentioning
confidence: 99%
“…2019; Lozovsky et al. 2020), there have been few formal attempts to integrate details of the environment into measurements of mutation effects and interactions. In this study, I introduce the “mutation effect reaction norm,” an abstraction that combines the reaction norm with mutation effects and physiological epistasis.…”
mentioning
confidence: 99%
“…In the simplest examples—third-order interactions—the interaction between two mutations changes depending upon whether a third mutation is present or not. Third-order interactions can occur among mutations in the same 19 , 26 , 27 or different 17 , 28 genes and make important contributions to diverse phenotypic traits such as growth and drug resistance 18 , 29 . We hypothesized that conceptually similar higher-order interactions might be occurring in cancer genomes, with mutations in a second gene (between gene interaction) altering the interaction between a mutation and CNA in a cancer gene (within gene interaction) (Fig.…”
Section: Resultsmentioning
confidence: 99%